Non-conventional thermoelectric generation potential in Bangladesh - Chowdhury, Ishmam Ahmed; Islam, Shadman Sakib; Hussain, Mufazzol; Hasnat, Ismam Bin (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.